Discovering the Discourse of Internet Political Memes - Brian McClure (Adult Education Research Conference, 2016)
With more adults engaging in political activity on social media sites such as Facebook, one popular form of communicating ideas–memes–has emerged. This form contributes to a particular discourse that has yet to be identified, examined, and clarified, the purpose of this paper.
Keywords: Political meme discourse; social media